Gerald M. Edelman and neurological anthropology presentation and discussion of his theory of the mind - Monserrat, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The essential question of anthropology, namely, what is the origin and nature of the human being, cannot be addressed without reference to the contributions of neurology. Hence we can speak of a «neurological anthropology». In recent years the work of Gerald Edelman has been an indisputable point of reference. First we will cover his epistemological framework, then his «Neural Darwinism» which defends the selective logic of biological evolution (selectionism) against the instructive logic of computation (instructionism), whether serial or PDP. The evolutionary emergence of memory (the «remembered present») is his basis for explaining the formation of primary consciousness, higher-order consciousness, and the mind. Finally we address his theory of the «dynamic core» and his explanation of the phenomenology of consciousness. Our discussion of Edelman’s theories considers various aspects and gaps in the history of evolution, the causes of the emergence of reason, and the arguable insufficiency of the notion that human beings are the product of the evolution of the animal mind.